PHENOMENOLOGICAL STUDY OF ENHANCING STUDENTS' LEARNING INTEREST THROUGH PROJECT-BASED LEARNING MODELS IN CHEMISTRY SUBJECT AT HIGH SCHOOLS IN SUKABUMI CITY (Forum for Linguistic Studies, 2024)
Chemistry lessons in high schools are still perceived as less popular, hence requiring educational management that can optimize students' interest in learning. This poses a unique challenge for teachers to enhance learning, one of which is project-based learning. This research aims to describe and analyze the optimization of students' interest through project-based learning in the chemistry subject. The study is qualitative, employing a phenomenological approach, and is also examined through the PDCA quality management theory by Edward Deming. Specifically, the research describes and analyzes planning, implementation, supervision, and follow-up on the optimization of PjBL in chemistry. The research is conducted at SMAN 1 Sukabumi and SMAN 2 Sukabumi. Data collection involves observation, interviews, and documentary studies. Data processing is assisted by the ATLAS.ti application, interpreted by researchers based on relevant supporting theories. The results indicate that in planning, teachers strategize topic selection, motivational planning, and create strategies to keep students engaged. For implementation, teachers play a guiding role, organizing groups to ensure smooth project-based learning. In the evaluation or supervision stage, teachers design assessments covering cognitive, psychomotor, and affective domains. As a follow-up effort for improvement, comprehensive evaluation and adjustments are made from planning to implementation and evaluation, focusing on refining planning and topic formulation. In conclusion, this study demonstrates that the optimization of teaching efforts is evident in teachers' management, executing each step of the learning process thoroughly. The key to enhancing student interest lies in the teacher's ability to organize project-based learning effectively.